2005
DOI: 10.1200/jco.2005.05.362
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Enhance Physical and Psychological Functioning Among Younger Women Who Are Ending Nonhormonal Adjuvant Treatment for Early-Stage Breast Cancer

Abstract: A B S T R A C T PurposeTo conduct a clinical trial to determine if an educational intervention and a nutritional intervention could enhance physical and psychological functioning among younger women completing treatment for early-stage breast cancer. Patients and MethodsYounger women (50 years of age or younger, N ϭ 252), within 2 months of having completed active nonhormonal adjuvant therapy, diagnosed with stage 0, I, or II breast cancer with 10 or fewer positive lymph nodes were randomly assigned to a three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 57 publications
7
98
0
3
Order By: Relevance
“…With these data, a new finding was the negative contribution of symptomsparticularly vaginal changes and fatigue-to women's worries and stress regarding body changes. Some quality of life studies have used the KPS or patient symptom reports (Dodd, 1988;Northouse, Kershaw, Mood, & Schafenacker, 2005;Scheier et al, 2005), but the use of the symptom-atology and toxicity listing is novel. These measures are costly, as medical expertise is required of the rater (e.g., a nurse specialist), yet they provide the benefit of objective, symptom-specific scales, unlike patient self reported health which is prone to reporting biases, including co-variation with negative affect (e.g., Denollet, 1991;Geisser, Roth, Theisen, Robinson, & Riley, 2000).…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…With these data, a new finding was the negative contribution of symptomsparticularly vaginal changes and fatigue-to women's worries and stress regarding body changes. Some quality of life studies have used the KPS or patient symptom reports (Dodd, 1988;Northouse, Kershaw, Mood, & Schafenacker, 2005;Scheier et al, 2005), but the use of the symptom-atology and toxicity listing is novel. These measures are costly, as medical expertise is required of the rater (e.g., a nurse specialist), yet they provide the benefit of objective, symptom-specific scales, unlike patient self reported health which is prone to reporting biases, including co-variation with negative affect (e.g., Denollet, 1991;Geisser, Roth, Theisen, Robinson, & Riley, 2000).…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…It may be that physical training has immediate effects on quality of life. Cognitivebehavioral therapy that confronts patients with personal worries and possibly increasing distress [13,28] might have long-term benefits [2,25,29]. Hence, the long-term effects of physical training combined with cognitive-behavioral therapy on quality of life may be greater compared to the effects of physical training alone.…”
Section: Introductionmentioning
confidence: 99%
“…This article examines whether the main intervention effects previously reported by Scheier et al 1 were moderated or conditioned by other factors.…”
Section: Introductionmentioning
confidence: 99%
“…A recently completed clinical trial, 1 the Breast Cancer Recovery Project (BCRP), has shown that two brief psychosocial interventions, one involving a series of educational sessions and one involving a series of nutritional sessions, can reduce depressive symptomatology and enhance physical functioning among younger women diagnosed with early-stage breast cancer. This article examines whether the main intervention effects previously reported by Scheier et al 1 were moderated or conditioned by other factors.…”
Section: Introductionmentioning
confidence: 99%